2005
DOI: 10.1007/s00701-005-0511-9
|View full text |Cite
|
Sign up to set email alerts
|

Presurgical octreotide treatment in acromegaly: no improvement of final growth hormone (GH) concentration and pituitary function. A long-term case-control study

Abstract: Presurgical octreotide treatment has no significant short- or long-term beneficial effect on GH concentration or pituitary function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(30 citation statements)
references
References 36 publications
0
29
0
1
Order By: Relevance
“…They were randomly divided into two groups. The experimental group comprised roadenomas and boosts the final cure rate is unclear [11][12][13][14][15]. In assessing the historical experience, analysis is challenging because most studies are retrospective.…”
Section: Patients (Table 2)mentioning
confidence: 99%
See 1 more Smart Citation
“…They were randomly divided into two groups. The experimental group comprised roadenomas and boosts the final cure rate is unclear [11][12][13][14][15]. In assessing the historical experience, analysis is challenging because most studies are retrospective.…”
Section: Patients (Table 2)mentioning
confidence: 99%
“…In assessing the historical experience, analysis is challenging because most studies are retrospective. The lack of direct comparisons, reliance on single GH values, a large range of octreotide doses utilized, and relatively small numbers of patients, are among the confounding factors [10,13,16]. Besides, the different proportion of patients with different tumor characters (size and invasiveness) makes these conclusions less instructive (Table 1).…”
Section: Patients (Table 2)mentioning
confidence: 99%
“…Tumor sizes were calculated by the Di Chiro and Nelson formula: volume = height × length × width × π/6 [22]. When T2-weighted images were available, the T2 intensity of the solid portion was visually compared with the cerebral grey and white matter in the adjacent temporal lobe.…”
Section: Magnetic Resonance Imaging (Mri) Studiesmentioning
confidence: 99%
“…Other studies, however, showed no benefit. 25,40 Further investigation is needed to define the role of presurgical pharmacological treatment in acromegaly.…”
Section: Primary or Secondary Pharmacological Therapymentioning
confidence: 99%